2019
DOI: 10.1016/j.bbrep.2019.100659
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations in the C-terminal portion of the B4GALNT2-encoded glycosyltransferase underlying the Sd(a−) phenotype

Abstract: Sd a is a high-frequency carbohydrate histo-blood group antigen, GalNAcβ1-4(NeuAcα2-3)Galβ, implicated in pathogen invasion, cancer, xenotransplantation and transfusion medicine. Complete lack of this glycan epitope results in the Sd(a−) phenotype observed in 4% of individuals who may produce anti-Sd a . A candidate gene ( B4GALNT2 ), encoding a Sd a -synthesizing β-1,4- N -acetylgalactosaminyltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…Furthermore, β1,4-N-acetylgalactosaminyltransferase 2 (B4GALNT2) is a biosynthetic enzyme of histo-blood group antigens Sda antigen, a natural component of the red blood cells in the healthy colon of a vast majority of people [ 71 ]. Prior studies have shown that the downregulation of B4GALNT2 can be a marker for colon and gastrointestinal cancers [ 71 , 72 ]. Direct upregulation of the B4GALNT2 gene level reduces the colon malignancy and the stem-associated malignant phenotype in a highly selective fashion [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, β1,4-N-acetylgalactosaminyltransferase 2 (B4GALNT2) is a biosynthetic enzyme of histo-blood group antigens Sda antigen, a natural component of the red blood cells in the healthy colon of a vast majority of people [ 71 ]. Prior studies have shown that the downregulation of B4GALNT2 can be a marker for colon and gastrointestinal cancers [ 71 , 72 ]. Direct upregulation of the B4GALNT2 gene level reduces the colon malignancy and the stem-associated malignant phenotype in a highly selective fashion [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…B4GALNT2 and its cognate antigen Sd a play various important roles in different contexts [ 18 ]. The vast majority of Caucasians express the Sd a antigen on erythrocytes and in a few other tissues, although a minority lack Sd a because of an inactivating germline mutation of B4GALNT2 [ 19 ]. At least two different transcripts that only differ in the first exon are generated from the B4GALNT2 gene.…”
Section: Introductionmentioning
confidence: 99%
“…We have identified a number of additional targets to be added to the next iteration of the panel which will increase its clinical utility. These include A4GALT Exon2a for P1/P2, 60 XG GATA box for Xg(a-), 12,13 SMYD1 associated with AnWj, 61 PIGT, 62 B4GALNT2 for the Sd a antigen, 40 and PRNP for the KANNO antigen. 39 Probes covering Exon 7 of CD177 will also be redesigned to match the HNA-2positive type, potentially improving genotyping for the HNA-2 system.…”
Section: Discussionmentioning
confidence: 99%
“…Gray rectangles indicate outputs related to SNV analyses and black rectangles indicate outputs related to copy number variant analysis reported after designing and testing the panel and therefore were not included. 39,40 The chosen targets and relevant chromosomal coordinates were presented to the Illumina concierge service who designed the initial panel probes to cover all coding regions. The probe panel was then reviewed and manually curated to include additional targets and ensure that all targets were covered before synthesis.…”
Section: Design Of Custom Sequencing Panelmentioning
confidence: 99%